Black Cohosh and Breast Cancer: A Systematic Review. (January 2014) - Fritz, Heidi; Seely, Dugald; McGowan, Jessie; Skidmore, Becky; Fernandes, Rochelle; Kennedy, Deborah A.; Cooley, Kieran; Wong, Raimond; Sagar, Stephen; Balneaves, Lynda G.; Fergusson, Dean
Background . Many women use black cohosh as a natural treatment for menopausal symptoms. However, controversy exists around safety in breast cancer, because of its purported estrogenic activity. We conducted a systematic review of black cohosh use in women with or at risk of breast cancer. Methods . We searched MEDLINE, Embase, the Cochrane Library, and AMED from inception to July 2012 and October 2012 for human interventional or observational data pertaining to the safety and efficacy of black cohosh in patients with or at risk of breast cancer, including an assessment of the effect of black cohosh on estrogen responsive tissues. Results . Of 450 records, we included 26 articles: 14 randomized controlled trials, 7 uncontrolled trials, and 5 observational studies.The evidence on efficacy for ho t flashes is divided, with some benefits seen when compared with baseline, but not when compared with placebo. Two observational studies found no association between black cohosh and risk of breast cancer, whereas 2 studies reported significant reductions in risk of primary breast cancer among postmenopausal women (adjusted odds ratio = 0.47, 95% confidence interval = 0.27-0.82), and risk of recurrence (adjusted hazard ratio = 0.75, 95% confidence interval = 0.63-0.89). Seventeen trials showed no significant impact on circulating hormone levels or proliferation in estrogen responsive tissues. Conclusions. Current evidence does not support an association between black cohosh and increased risk of breast cancer. There is a lack of evidence supporting the efficacy of black cohosh for reduction of hot flashes in breast cancer patients. Given conflicting but promising results, and apparent safety, further research is warranted.